KNOWLEDGE OF REPRODUCTIVE HEALTH WITH EARLY MARRIAGE ON CHILDBEARING AGE (PUS) (Al Insyirah International Scientific Conference on Health, 2021)
The problems of reproductive health knowledge with the incidence of early marriage in Indonesia is still found in rural areas, among others influenced by the knowledge, the characteristics of the physical environment, economic and social culture. Based on the results of a preliminary study in the Village Purwawinangun, interviews were conducted to 10 PUS known to most of them do not know the impact of early marriages on reproductive health. The purpose of this study to identify there a relationship between knowledge about reproductive health with pernikhan incident early on EFA in Sub Purwawinangun. Research type used is analytic with cross sectional design. The respondents totaled 135 respondents were taken by total population sampling. Data were collected using secondary data is data that is seen from the number of marriages in the can from the village and primary data using a questionnaire with interview research shows that the level of knowledge about reproductive health that respondents with good knowledge level of 14.8% (20 respondents), just as much as 71.2% (96 respondents) and less than 14% (19 respondents). Conclusion The level of knowledge about reproductive health that respondents with good knowledge level of 14.8%), just as much as 71.2% and less than 14%). The results of this study are expected to be material information or input for EFA in the village Puerwawinangun, so they are better prepared to plan a wedding.
Keywords: reproductive health; the incidence of early marriage